2016
DOI: 10.1097/cej.0000000000000196
|View full text |Cite
|
Sign up to set email alerts
|

Length but not transverse diameter of the excision specimen for high-grade cervical intraepithelial neoplasia (CIN 2–3) is a predictor of pregnancy outcome

Abstract: The objective of this study was to analyze the impact of cone characteristics (depth, transverse diameter, and volume) on subsequent pregnancies after the loop electrosurgical excision procedure (LEEP) for cervical intraepithelial neoplasia (CIN 2-3). Pregnancy outcomes (preterm birth, gestational age at birth, mode of delivery, and birth weight) of 501 women with singleton gestations and no previous preterm birth or history of late miscarriage, who had previously undergone a single LEEP for CIN 2-3, were retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 32 publications
4
20
0
Order By: Relevance
“…We did not nd an association between having a prior cervical excision procedure and Caesarean sections delivery(p = 0.484), similar with vast previous studies [10][11][12][13]. Theoretically, having a prior cervical excision procedure can affect the coordination of uterine contractions, which is more likely to result in dystocia and increases the risk of both forceps delivery and Caesarean sections delivery.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We did not nd an association between having a prior cervical excision procedure and Caesarean sections delivery(p = 0.484), similar with vast previous studies [10][11][12][13]. Theoretically, having a prior cervical excision procedure can affect the coordination of uterine contractions, which is more likely to result in dystocia and increases the risk of both forceps delivery and Caesarean sections delivery.…”
Section: Discussionsupporting
confidence: 88%
“…It happens because cervix is a growing organ [19]; because uterus can repair itself in a short time with abundant vascularity; because during the long period of pregnancy, uterus grows slowly and has enough time to repair itself to suit pregnancy and delivery condition. However, Liverani et al [13] reported that women who became pregnant within 12 months since LEEP showed a signi cantly lower rate of cesarean sections (31.6% vs. 44.3%, P = 0.03) compared with women with a longer time interval from LEEP to pregnancy. Therefore, further study is still needed to increase the sample size, layer the time interval between cervical excision procedure and pregnancy, and observe the delivery mode between different layers of the time interval.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Considering this, wider and cylindrical excisions are often necessary for conservative treatment of AIS, whereas the different biological behavior of squamous intraepithelial lesion can allow the execution of smaller excisions, with the need of a reduced disease-free margin. Moreover, the growing evidence about the increased risk of prematurity and perinatal mortality for increasing cone dimensions 7,8 imposes the need to perform smaller excisions in women with childbearing potential in order to reduce the functional impairment of the uterine cervix. Limited dimensions seem also to determine better recovery of cervical dimensions after excisional procedures, probably reducing the risk of subsequent adverse obstetric outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This operation has been applied in the treatment of early-stage cervical invasive cancer and CIN in recent years. The pathological incisal margin condition is the important index for CIN development ( 7 ). It has been proven in the clinic ( 8 ) that patients with a positive incisal margin have poor prognosis, and it is a high risky factor for potential residue and relapse of the disease.…”
Section: Discussionmentioning
confidence: 99%